(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the theoretical foundations and practical methodologies of ethnically neutral, culturally responsive English language teaching (ELT) in the ethnically and linguistically diverse educational landscape of Uzbekistan. While the Republic of Uzbekistan is predominantly Uzbek-speaking, its technicum and secondary school classrooms are frequently composed of learners from multiple ethnic, linguistic, and cultural backgrounds — including Uzbek, Tajik, Kazakh, Karakalpak, Russian, Korean, and other minority communities — each carrying distinct linguistic schemas, culturally embedded learning styles, and historically shaped relationships with the English language and with dominant-group schooling cultures. This article argues that effective English language teaching in such contexts must operate simultaneously at two levels: it must be culturally responsive — acknowledging, validating, and strategically utilising learners’ diverse cultural and linguistic resources — while remaining ethnically non-deterministic, refusing to reduce individual learners to cultural or ethnic stereotypes.